CLASSROOM MANAGEMENT AS A PURPOSEFUL SYSTEM OF EDUCATION - Sharipova, Sitora Shukhratovna; Chorieva, Rushana Shukhratovna; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
This article is dedicated to the primary factors of study room management, it discusses the dreams and objectives, features and sorts of school room management.